Dante's Comedy in Dostoevsky's Crime and Punishment - Caterina Corbella (Достоевский и мировая культура: Филологический журнал, 2022)
The article is dedicated to the possible presence of Dante’s Comedy in Dostoevsky’s novel Crime and Punishment. After a brief introduction dedicated to the existing research on the matter and to enumerate some of the macroscopical elements that are common to both works, the author focuses on two passages of Dostoevsky’s text. The first one is Raskolnikov’s decision to go down in the tavern, that is very similar to Dante’s entrance in the Inferno, as “going down” is the only (even if unexpected) way to salvation for both characters. The article goes on underlining some details that allows to think that the scene presents more than casual similarities. The second passage are Porfiry Petrovich’s words in the second chapter of the sixth part of the novel, where a great number of allusions to Dante can be found, starting with the recurring remark about the Pillars of Hercules. Thanks to the analysis of this passage, it is possible to submit the hypothesis that Dostoevsky had in mind not only the Inferno, but (at least) also Dante’s Purgatorio while creating the novel. Here can also be found a new element in favor of the recently proposed convergence between the figures of Raskolnikov and Dante’s Mahomet. The notes to the article present other elements that can possibly be identified as allusions to Dante.